Development of Electronic Handout Media Using the Double Loop Problem Solving (DLPS) Model on Physics Material For Class X High School Student - Miranda Agustina; Yuberti Yuberti; Muhammad Ridho Syarlisjiswan (Jurnal Pembelajaran Fisika, 2023)
This study aims to develop electronic handout media with the Double Loop Problem Solving (DLPS) model on physical materials, namely energy source materials for tenth-grade high school students to determine the feasibility and attractiveness of the electronic handout being developed. This electronic handout was created using Smart Apps Creator which is a mobile application for Android and iOS without a programming code and the form is html.5 and exe. This study uses the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. This research was conducted in two Bandar Lampung tenth-grade schools and was validated by material and media experts. This study aims to get a validation score of 83% in the "very decent" category from material experts and 79% in the "very decent" category from media experts. While the results of development trials obtained a score of 78% in the "very interesting" category. Educator responses reached 89% in the "very interesting" category. The conclusion of this study is that the electronic handouts developed are very practical and very interesting to be used as learning media.Keywords: Double Loop Problem Solving (DLPS), Electronic Handouts, Smart Apps Creator (SAC), Learning MediaDOI: http://dx.doi.org/10.23960/jpf.v11.n1.202303